Pengaruh Model Think Pair Share dengan Media Lagu Sahabat Sejati terhadap Kemampuan Menulis Cerpen Siswa Kelas XI MAS Proyek UNIVA Medan - Khairunnisa Lubis (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2021)
This study aims to describe the ability to write short stories using the Think Pair Share learning model with the media song true friend of class XI MAS students in the UNIVA Medan project for the 2019 / 2020 academic year, to describe the ability to write short stories using the Think Pair Share learning model with video media for class XI MAS students. The UNIVA Medan project for the 2019 / 2020 academic year, to describe whether there is a significant influence on the ability to write short stories using the Think Pair Share learning model with the song media for the true friend of XI MAS students. The UNIVA Medan project for the 2019 / 2020 academic year. The sample in this study was 60 students. 2. From the results of data processing, the average value of the experimental class is 72.3 while the control class is 64.6. Thus it can be said that the results of learning to write short stories in the experimental class are higher than the control class. After testing the hypothesis, the value of tcount = 3.701 is then adjusted to ttable at a significant level = 5% with dk = (n1+n2) – 2 = (30+30 – 2) = 58, then the significant level is 5% = 2.002 ( by interpolation). Then compared between tcount and ttable, it was obtained that tcount 3.701 > ttable 2.002 so that Ho (Nil Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted.